Analisis Pelaksanaan Program Kejar Paket Tuntaskan Putus Sekolah Pada Peserta Didik Paket C di Sanggar Kegiatan Belajar Kabupaten Gresik, Jawa Timur - Anggraini, Nita Julia; Riyanto, Yatim (Jurusan Pendidikan Luar Sekolah Fakultas Ilmu Pendidikan UNESA, 2023)
Non-formal education is a learning process that takes place in an organized way outside the formal education system/school, one of which is package C equivalence education. The Gresik Regency Government has provided an innovative program, namely the